Pelatihan Penulisan Karya Tulis bagi Guru SMA Hang Tuah 3 Mataram - Tri Setianingsih; Siti Syafiâ€™atul Qomariyah; Sri Ariani; Muhamad Suhaili (Jurnal Pengabdian UNDIKMA, 2020)
This community service activity was held in SMA Hang Tuah 3 Mataram, NTB Province.Â  This school is located approximately 6 km from the location of the team. Located in the center of Mataram city. The purpose of this activity is to make the teachers in SMA Hang Tuah 3 Mataram know the ways of writing and the forms of a paper and ultimately be able to automatically express their ideas, ideas and experiences during the teaching and learning process into a scientific writing eligible to be published in an ISSN journal. The training activities were held because to the collaboration of both parties namely SMA Hang Tuah 3 Mataram and the dedication team from IKIP Mataram.